A Note on Marx and the Trade Cycle - Wilson, John D. (Review of Economic Studies, 1938)
A Note on Marx and the Trade Cycle John D. Wilson John D. Wilson Cambridge, Mass. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 5, Issue 2, February 1938, Pages 107–113, https://doi.org/10.2307/2967524 Published: 01 February 1938